Research on the Application of Differential Privacy Algorithm in Financial AI Security Risk Prevention and Response - Qin, Kaijie (International Journal of Computer Science and Information Technology, 2024)
This research focuses on the field of financial AI security, and discusses the role of cryptographic algorithms in risk prevention and response. With the wide application of artificial intelligence technology, the financial industry is facing unprecedented security challenges. This research aims to reveal potential AI security risks in the financial system and propose solutions based on cryptographic algorithms to enhance the security and stability of the financial system.